2019
DOI: 10.1093/nar/gkz262
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-associated R-loop affects transcription and differentiation in breast luminal epithelial cells

Abstract: BRCA1 -associated basal-like breast cancer originates from luminal progenitor cells. Breast epithelial cells from cancer-free BRCA1 mutation carriers are defective in luminal differentiation. However, how BRCA1 deficiency leads to lineage-specific differentiation defect is not clear. BRCA1 is implicated in resolving R-loops, DNA-RNA hybrid structures associated with genome instability and transcriptional regulation. We recently showed that R-loops are preferentially accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 90 publications
3
34
0
Order By: Relevance
“…In one study, it was shown that the binding of GADD45A to the R-loop in the TCF21 promoter triggers local DNA demethylation and TCF21 expression (Arab et al 2019). In the other study, BRCA1-dependent R-loop mitigation contributes to luminal cell-specific transcription and differentiation (Chiang et al 2019). Mutation of BRCA1 causes R-loops to accumulate at enhancer and/or promoter regions of luminal fate genes, which in turn down-regulate expression of luminal fate genes.…”
Section: A B Cmentioning
confidence: 97%
“…In one study, it was shown that the binding of GADD45A to the R-loop in the TCF21 promoter triggers local DNA demethylation and TCF21 expression (Arab et al 2019). In the other study, BRCA1-dependent R-loop mitigation contributes to luminal cell-specific transcription and differentiation (Chiang et al 2019). Mutation of BRCA1 causes R-loops to accumulate at enhancer and/or promoter regions of luminal fate genes, which in turn down-regulate expression of luminal fate genes.…”
Section: A B Cmentioning
confidence: 97%
“…Just to mention some of them, BRCA1 and BRCA2 proteins, which are associated with breast and ovarian cancer development, have a role in R-loop regulation at promoters and terminators of transcribed genes and at DSBs ( Bhatia et al, 2014 ; Hatchi et al, 2015 ; D’Alessandro et al, 2018 ; Shivji et al, 2018 ). Interestingly, mutations in BRCA1 cause R-loop accumulation at specific genes and an altered transcription rate, and these events seem to be directly implicated in tumorigenesis ( Zhang et al, 2017 ; Chiang et al, 2019 ). In BRCA2-deficient cells, RNase H1 overexpression reduces formaldehyde-induced replication fork stalling as well as structural chromosomal aberrations formed under these conditions, thus suggesting that R-loops contribute, at least partially, to the pathogenic effects of BRCA2 inactivation ( Tan et al, 2017 ).…”
Section: R-loop and Diseasesmentioning
confidence: 99%
“…Recently, the MRN complex was found to be involved in the formation of R-loops but not dependent on the nuclease activity of MRE11, showing that the MRN complex suppresses R-loop formation and is required for FANCM and BLM recruitment to R-loop sites (Chang et al 2019). Similarly, CtIP, BRCA1 and BRCA2 prevent R-loop accumulation in eukaryotic cells (Makharashvili et al 2018;Chiang et al 2019;Bhatia et al 2014). MRE11 is also involved in immunoregulation.…”
Section: Biological Functions Of Mre11mentioning
confidence: 99%